Glass and preparation method thereof, glass fiber and electronic device

By adjusting the proportion of glass components and optimizing the glass structure, the problem that the dielectric constant and dielectric loss of existing glass in the high-frequency band cannot meet the fifth generation wireless communication technology, and the dielectric constant, dielectric loss and thermal expansion are achieved The optimization of coefficients meets the requirements of communication technology.

CN119390350APending Publication Date: 2025-02-07QINGYUAN CSG NEW ENERGY SAVING MATERIALS CO LTD +2

Patent Information

Application Number
CN202411457674.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing dielectric constant and dielectric loss of low-dielectric constant glass in the high-frequency band cannot meet the requirements of the fifth generation wireless communication technology.

Method used

By adjusting the component ratio of the glass, including SiO2, B2O3, P2O5, Al2O3, Na2O, MgO, CaO, TiO2 and Y2O3, the structure of the glass is optimized to reduce the dielectric constant, dielectric loss and thermal expansion coefficient.

Benefits of technology

The dielectric constant under 1MHz is achieved with a dielectric constant of less than or equal to 5.5, a dielectric loss of less than or equal to 3.8×10-3, and a thermal expansion coefficient of less than 1500°C, meeting the requirements of the fifth generation wireless communication technology for glass substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides glass and a preparation method thereof, glass fiber and an electronic device. The glass is prepared from the following components in percentage by mass: 56 percent to 64 percent of SiO2, 4 percent to 9 percent of B2O3, 0.1 percent to 1 percent of P2O5, 10 percent to 17 percent of Al2O3, 2 percent to 7 percent of Na2O, 4 percent to 8 percent of MgO, 4 percent to 10 percent of CaO, 0.1 percent to 1.5 percent of TiO2 and 0.01 percent to 1 percent of Y2O3. According to the present invention, the types and the mass percentages of the glass components are regulated and controlled, the components cooperate with each other and have the synergistic effect, and the stability of the frame-shaped structure in the glass structure is improved so as to improve the dielectric property and the thermal property of the glass product; further, the requirements of the fifth-generation wireless communication technology on the glass substrate can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of glass technology, and in particular to glass and a preparation method thereof, glass fiber and electronic devices. Background Art

[0002] The fifth generation of wireless communication technology (5G) has a transmission rate of up to 10Gb / s, ultra-large network capacity, and ultra-short latency of milliseconds, enabling a variety of novel and complex applications.

[0003] Wireless communication modules include functions such as signal reception and transmission, modulation and demodulation, power amplification, and filtering, which require the devices used to have characteristics such as larger bandwidth, higher frequency, and more compact size. In order to further increase the speed of signal propagation, the communication band is developing towards the high frequency band, electronic devices are developing towards miniaturization and lightweight, and electronic information and signals are developing towards large capacity, high density, high speed, and low loss; therefore, low-dielectric glass as the base material of communication devices is required to have lower dielectric constant and dielectric loss in the high frequency band.

[0004] The substrate materials commonly used in 5G communication technology, such as low dielectric constant glass, generally have a dielectric constant greater than 6.0, which cannot meet the requirements of electronic devices in 5G wireless communication technology for glass substrates; therefore, traditional technologies still need to be improved. Summary of the invention

[0005] Based on this, one or more embodiments of the present application provide a glass with low dielectric constant, dielectric loss and thermal expansion coefficient, a preparation method thereof, a glass fiber and an electronic device.

[0006] According to a first aspect of an embodiment of the present application, a glass is provided, which comprises the following components, measured by mass percentage: SiO2 56%~64%, B2O3 4%~9%, P2O5 0.1%~1%, Al2O3 10%~17%, Na2O 2%~7%, MgO 4%~8%, CaO 4%~10%, TiO2 0.1%~1.5% and Y2O3 0.01%~1%.

[0007] In one embodiment, the glass comprises the following components, by mass percentage: SiO2 58%~62%, B2O3 5%~8%, P2O5 0.4%~0.7%, Al2O3 12%~16%, Na2O 3%~6%, MgO 5%~7%, CaO 5%~9%, TiO2 0.1%~0.9% and Y2O3 0.01%~0.5%.

[0008] In one embodiment, the glass comprises the following components, by mass percentage: SiO2 58%~62%, B2O3 5%~8%, P2O5 0.4%~0.7%, Al2O3 12%~16%, Na2O 3.5%~5.5%, MgO 5.5%~6.5%, CaO 6%~8%, TiO2 0.1%~0.5% and Y2O3 0.01%~0.3%.

[0009] In one embodiment, the sum of the mass percentages of the Na2O, the MgO and the CaO is a, the mass percentage of the TiO2 is b, the mass percentage of the Y2O3 is c, and e is satisfied. (-a) The value of -ln(b)-ln(c) is 0.1~6.

[0010] In one embodiment, the glass further comprises the following components, measured by mass percentage: 0.1% to 0.5% of a clarifier;

[0011] Optionally, the clarifier is selected from NaCl.

[0012] In one embodiment, the glass satisfies at least one of the following characteristics:

[0013] (1) At 1 MHz, the dielectric constant of the glass is less than or equal to 5.5;

[0014] (2) At 1 MHz, the dielectric loss of the glass is less than or equal to 3.8×10 -3 ;

[0015] (3) In 10 2.0 dPa.s, the melting temperature of the glass is less than 1500°C.

[0016] According to a second aspect of an embodiment of the present application, a method for preparing glass is provided, comprising the following steps:

[0017] Providing raw materials according to the above-mentioned glass components, and mixing the raw materials to prepare a mixture;

[0018] melting the mixture to prepare molten glass; and

[0019] The glass liquid is subjected to molding and annealing treatment in sequence to obtain the glass.

[0020] In one embodiment, the annealing treatment is performed at a temperature of 560°C to 620°C.

[0021] According to a third aspect of the embodiments of the present application, a glass fiber is provided, wherein the material of the glass fiber includes the above-mentioned glass.

[0022] According to a fourth aspect of the embodiments of the present application, there is provided an electronic device comprising the above-mentioned glass or the above-mentioned glass fiber.

[0023] Compared with the traditional technology, this application has the following beneficial effects:

[0024] The present application regulates the types and mass percentages of glass components, and the components cooperate and work synergistically with each other, thereby improving the stability of the frame structure in the glass structure, thereby being able to improve the dielectric and thermal properties of the glass product; thereby being able to meet the requirements of the fifth generation wireless communication technology for glass substrates. DETAILED DESCRIPTION

[0025] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.

[0027] In the present application, "further", "further", "particularly" and the like are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of the present application.

[0028] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0029] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0030] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1 to 10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.

[0031] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0032] In the present application, %(w / w) and % both represent weight percentage, %(v / v) refers to volume percentage, and %(w / v) refers to mass volume percentage.

[0033] The first aspect of the present application provides a glass, which comprises the following components, calculated by mass percentage: SiO2 56%~64%, B2O3 4%~9%, P2O5 0.1%~1%, Al2O3 10%~17%, Na2O 2%~7%, MgO 4%~8%, CaO 4%~10%, TiO2 0.1%~1.5% and Y2O3 0.01%~1%.

[0034] SiO2 is a glass-forming oxide, which forms an irregular continuous network with the structural unit of silicon-oxygen tetrahedron as the skeleton of glass; the dielectric loss of glass is mainly determined by the compactness of the network structure. The tighter the network structure, the smaller the dielectric loss. If the content of SiO2 is too low, the integrity of the glass network will be poor, the external body ions will easily migrate in the glass, the ion displacement polarization and the orientation polarization of the polar bond will rise, causing electromagnetic signal absorption, and the electromagnetic wave transmittance will decrease, and the dielectric constant and dielectric loss will also increase. At the same time, the thermal expansion coefficient of the glass will increase too much, and the forming and chemical resistance will decrease, there will be a tendency to crystallize, and the strength of the glass will decrease; if the content of SiO2 is too high, the glass melting and clarification temperature will be higher, and the viscosity will rise, it will be difficult to homogenize the glass, which is not suitable for glass forming process manufacturing, and the production cost is high. Therefore, the present application limits the mass percentage of SiO2 to 56%~64%.

[0035] It can be understood that the mass percentage of SiO2 is "56% to 64%", that is, the minimum and maximum values ​​in the range of 56% to 64%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values: 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63% or 64%; or a range composed of any two of these values, such as: 58% to 63%.

[0036] In some optional examples, the mass percentage of SiO2 is 58%~62%.

[0037] B2O3 is also a glass-forming oxide. Boron-oxygen tetrahedrons are a frame-like structure with a tight structure. They can effectively reduce the absorption and attenuation of electromagnetic signals when passing through a glass substrate, reduce the thermal expansion coefficient of the glass, and improve its thermal stability and chemical stability. Introducing a small amount of B2O3 can reduce the polarizability of the glass to reduce the dielectric constant and dielectric loss of the glass; if the B2O3 content is low, there will be insufficient free oxygen in the glass, which will increase the number of boron-oxygen triangles in the layered structure, reduce the content of boron-oxygen tetrahedrons, make the glass network structure loose, and make the chemical properties unstable; and excessive B2O3 content will increase the volatilization, which can easily cause uneven glass composition. Therefore, this application limits the mass percentage of B2O3 to 4%~9%.

[0038] It can be understood that the mass percentage of B2O3 is "4% to 9%", that is, the minimum and maximum values ​​in the range of 4% to 9%, and every value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values: 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5% or 9%; or a range composed of any two of these values, such as: 6% to 8%.

[0039] In some optional examples, the mass percentage of B2O3 is 5%~8%.

[0040] P2O5 is an important component of the network structure of glass materials. When a certain amount of P2O5 is introduced when the content of Al2O3 is low, it can enter the glass network and replace SiO2 in the glass with aluminum phosphate (AlPO4); compared with the silicon-oxygen tetrahedron in the glass network structure, AlPO4 has a large volume, and the polarizability of P2O5 is smaller than that of SiO2, which can make the dielectric constant and dielectric loss of the glass smaller. If the content of P2O5 is too low, the dielectric constant will increase and the dielectric loss will rise significantly; the introduction of too much P2O5 will significantly increase the thermal expansion coefficient, the melting temperature of the glass will increase, and the glass will be prone to devitrification and phase separation. Therefore, this application limits the mass percentage of P2O5 to 0.1%~1%.

[0041] It can be understood that the mass percentage of P2O5 is "0.1%~1%", that is, the minimum and maximum values ​​in the range of 0.1%~1%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values: 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; or a range composed of any two of these values, such as: 0.2%~0.8%.

[0042] In some optional examples, the mass percentage of P2O5 is 0.4%~0.7%.

[0043] Al2O3 belongs to the intermediate oxide, which can reduce the crystallization tendency of glass, improve the chemical stability, thermal stability, mechanical strength and hardness of glass, and is also a necessary component to improve the elastic modulus of tensile glass. If there is too much Al2O3, it is difficult to obtain glass with long material properties, making glass molding more difficult. Since the aluminum oxide tetrahedron is more stable than the boron oxide tetrahedron structure, aluminum ions will preferentially obtain free oxygen to form aluminum oxide tetrahedrons in the glass structure unit, and then the excess free oxygen will be transformed into boron oxide tetrahedrons with boron oxide triangles, but due to the large volume of aluminum oxide tetrahedrons, it is not conducive to the reduction of dielectric loss of glass. Therefore, the present application limits the mass percentage of Al2O3 to 10%~17%.

[0044] It can be understood that the mass percentage of Al2O3 is "10% to 17%", that is, the minimum and maximum values ​​in the range of 10% to 17%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values ​​10%, 11%, 12%, 13%, 14%, 15%, 16% or 17%; or a range composed of any two of these values, such as: 11.5% to 16.5%.

[0045] In some optional examples, the mass percentage of Al2O3 is 12%~16%.

[0046] Na2O is an oxide and solubilizer outside the glass network. It can provide free oxygen to break Si-O bonds, thereby reducing the viscosity and melting temperature of the glass, but it has a higher polarizability, dielectric loss and thermal expansion coefficient. If the content of Na2O is too high, the number of broken bonds in the glass may increase, resulting in an incomplete glass network structure, thereby increasing the dielectric constant, dielectric loss and linear thermal expansion coefficient, and reducing chemical stability; and the amount of Na2O volatilization increases, resulting in uneven glass composition. If the content of Na2O is too low, it is not conducive to the melting and molding of the glass. Therefore, the present application limits the mass percentage of Na2O to 2%~7%.

[0047] It can be understood that the mass percentage of Na2O is "2% to 7%", that is, the minimum and maximum values ​​in the range of 2% to 7%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values ​​2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5% or 7%; or a range composed of any two of these values, such as: 2.5% to 6.5%.

[0048] In some optional examples, the mass percentage of Na2O is 3%~6%.

[0049] Furthermore, the mass percentage of Na2O is 3.5% to 5.5%.

[0050] MgO is a network exo-oxide, which helps to lower the melting point of glass, reduce the viscosity of glass at high temperature, promote the melting and clarification of glass, improve uniformity, and increase hydrolysis resistance. MgO can also stabilize glass, improve the durability of glass, prevent glass from crystallizing, inhibit the movement of alkali metal ions in glass, and also has the function of increasing the elastic modulus of glass. MgO can enhance the stability of the glass network space at low temperatures and reduce the thermal expansion coefficient of glass to a certain extent, but too much content will cause the glass network to break and the dielectric properties to deteriorate. Therefore, this application limits its mass percentage to 4%~8%.

[0051] It can be understood that the mass percentage of MgO is "4% to 8%", that is, the minimum and maximum values ​​in the range of 4% to 8%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values ​​4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5% or 8%; or a range consisting of any two of these values, such as: 4.5% to 7.5%.

[0052] In some optional examples, the mass percentage of MgO is 5% to 7%.

[0053] Furthermore, the mass percentage of MgO is 5.5% to 6.5%.

[0054] CaO can relax and break the network formed by silicon-oxygen tetrahedron [SiO4], improve the melting properties of glass at high temperatures or make the glass less likely to lose clarity, but too much content will cause the glass network to break, affecting its weather resistance and deteriorating dielectric properties. Therefore, the mass percentage of CaO is limited to 4% to 10% in this application.

[0055] It can be understood that the mass percentage of CaO is "4% to 10%", that is, the minimum and maximum values ​​in the range of 4% to 10%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values ​​4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5% or 10%; or a range consisting of any two of these values, such as: 4.5% to 7.5%.

[0056] In some optional examples, the mass percentage of CaO is 5% to 9%.

[0057] Furthermore, the mass percentage of CaO is 6% to 8%.

[0058] Y2O3 and TiO2 can aggregate anion clusters in the glass, so that the glass network structure can effectively reduce the deformation of the electron cloud under the action of the external electric field, and can also make the migration of external ions along the direction of the electric field more difficult, thereby reducing the dielectric constant of the glass, improving the melting and clarification effect of the glass, and increasing the Young's modulus of the glass.

[0059] Understandably, the mass percentage of Y2O3 is "0.01%~1%", that is, the minimum and maximum values ​​in the range of 0.01%~1%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values ​​0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; or a range composed of any two of these values, such as: 0.05%~0.8%.

[0060] In some optional examples, the mass percentage of Y2O3 is 0.01%~0.5%.

[0061] Furthermore, the mass percentage of Y2O3 is 0.01%~0.3%.

[0062] It can be understood that the mass percentage of TiO2 is "0.1% to 1.5%", that is, the minimum and maximum values ​​in the range of 0.1% to 1.5%, and each value between the minimum and maximum values. Specifically including but not limited to the point values ​​in the embodiment and the following point values ​​0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4% or 1.5%; or a range composed of any two of these values, such as: 0.5% to 1.2%.

[0063] In some optional examples, the mass percentage of TiO2 is 0.1%~0.9%.

[0064] Furthermore, the mass percentage of TiO2 is 0.1%~0.5%.

[0065] In some embodiments, the glass includes the following components: SiO2 58%~62%, B2O3 5%~8%, P2O5 0.4%~0.7%, Al2O3 12%~16%, Na2O 3%~6%, MgO 5%~7%, CaO 5%~9%, TiO2 0.1%~0.9% and Y2O3 0.01%~0.5%.

[0066] In some embodiments, the glass includes the following components: SiO2 58%~62%, B2O3 5%~8%, P2O5 0.4%~0.7%, Al2O3 12%~16%, Na2O 3.5%~5.5%, MgO 5.5%~6.5%, CaO 6%~8%, TiO2 0.1%~0.5% and Y2O3 0.01%~0.3%.

[0067] In some embodiments, the sum of the mass percentages of Na2O, MgO and CaO is a, the mass percentage of TiO2 is b, the mass percentage of Y2O3 is c, and e is satisfied. (-a) The value of -ln(b)-ln(c) is 0.1~6.

[0068] As an example, e (-a) The value of -ln(b)-ln(c) can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 2, 3, 4, 5 or 6; or a range consisting of any two of these values.

[0069] In some of the embodiments, the glass further comprises the following components, calculated by mass percentage: 0.1% to 0.5% of a clarifier.

[0070] It is understandable that adding clarifiers can effectively remove bubbles in the glass liquid and improve the quality and transparency of the glass. The use of clarifiers during melting is not affected by the melting or molding atmosphere, and a small amount of clarifiers will not affect the service life of the kiln.

[0071] In some of these embodiments, the clarifier is selected from NaCl.

[0072] The glass containing the above-mentioned specific components can be obtained in the traditional flat glass manufacturing process, and its manufacturing process includes but is not limited to float forming process, overflow down-draw method, draw-up method, flat-draw method, rolling method, etc. The melting method can be selected from full electric melting, electric melting + full oxygen combustion, electric melting + oxygen-enriched combustion and flame + electric melting, etc.

[0073] In some embodiments, the glass has a dielectric constant of less than or equal to 5.5 at 1 MHz.

[0074] In some embodiments, the dielectric loss of the glass at 1 MHz is less than or equal to 3.8×10 -3 .

[0075] In some embodiments, the glass is 2.0 The melting temperature under dPa.s conditions is less than 1500℃.

[0076] A second aspect of the present application provides a method for preparing glass, comprising steps S10 to S30.

[0077] Step S10: providing raw materials according to the above-mentioned glass components, and mixing the raw materials to prepare a mixture.

[0078] Step S20: Melting the mixture to prepare molten glass.

[0079] Step S30: sequentially forming and annealing the glass liquid to obtain glass.

[0080] In some embodiments, in step S20, the temperature of the annealing treatment is 560°C to 620°C.

[0081] As an example, the temperature of the annealing process may be 560°C, 561°C, 562°C, 563°C, 564°C, 565°C, 566°C, 567°C, 568°C, 569°C, 570°C, 580°C, 590°C, 600°C, 610°C or 620°C.

[0082] A third aspect of the present application provides a glass fiber, wherein the material of the glass fiber includes the above-mentioned glass.

[0083] A fourth aspect of the present application provides an electronic device, comprising the above-mentioned glass or the above-mentioned glass fiber.

[0084] The glass of the present application has the advantages of low dielectric constant, low dielectric loss and low thermal expansion coefficient, and can meet the requirements of the fifth generation wireless communication technology for the communication device substrate. Therefore, the electronic device containing the glass can be used in the fifth generation wireless communication technology.

[0085] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.

[0086] Embodiment 1~embodiment 30:

[0087] (1) Raw material preparation: According to the mass percentages and raw material types recorded in Tables 1 to 4, weigh a mixture with a total weight greater than 500 g and stir and mix thoroughly.

[0088] (2) Melting: Place the mixture into a platinum crucible larger than 400 mL, place the platinum crucible into a silicon-molybdenum furnace, heat it to the melting temperature of 1500°C, and melt and clarify it for more than 4 to 8 hours to homogenize it and cast it into a mold for casting.

[0089] (3) Annealing: The formed glass is placed in an annealing furnace for annealing at a temperature of 560°C to 620°C to obtain a glass sample.

[0090] (4) Thermal properties test: The glass samples prepared in Examples 1 to 30 were subjected to high temperature viscosity tests respectively, using a high temperature viscometer from ORTON, USA, to obtain temperature-viscosity curve data, and further obtain a viscosity-temperature fitting curve within the glass float forming temperature range to determine the glass melting temperature Tm (10 2.0 dPa.s). With reference to GB / T16920-2015, the thermal expansion performance was tested using the PC402L horizontal dilatometer from NETZSCH, Germany, to obtain the thermal expansion coefficient CTE (50℃~300℃) and transition temperature Tg.

[0091] (5) Dielectric property test: Referring to the test method described in ASTM-D150-18, the glass to be tested was processed into a rectangular sheet sample of 10.16 mm×22.86 mm×1 mm, and the dielectric constant and dielectric loss of the glass sample at a frequency of 1 MHz were measured using a PNA-N5234A vector network analyzer and a waveguide method. The test results of the thermal properties and dielectric properties of the glasses prepared in Examples 1 to 30 are shown in Tables 1 to 4.

[0092] Table 1

[0093]

[0094] Table 2

[0095]

[0096] Table 3

[0097]

[0098] Table 4

[0099]

[0100] Comparative Examples 1-7: Glass products were prepared by referring to the preparation methods described in Examples 1-30 and the mass percentages of components described in Table 5. The performance test results are shown in Table 5.

[0101] Table 5

[0102]

[0103] As shown in Tables 1 to 5, in Examples 1 to 30 of the present application, by controlling the glass components and improving the frame structure in the glass structure, the dielectric constant of the prepared glass at 1 MHz is less than or equal to 5.5, and the dielectric loss is less than or equal to 3.8×10 -3 , Tm(10 2.0 dPa.s)≤1500℃.

[0104] Further, Examples 8 to 29 satisfy the following conditions: the mass percentage of SiO2 is 58% to 62%, the mass percentage of B2O3 is 5% to 8%, the mass percentage of P2O5 is 0.4% to 0.7%, the mass percentage of Al2O3 is 12% to 16%, the mass percentage of Na2O is 3% to 6%, the mass percentage of MgO is 5% to 7%, the mass percentage of CaO is 5% to 9%, the mass percentage of TiO2 is 0.1% to 0.9%, the mass percentage of Y2O3 is 0.01% to 0.5%, and e -(Na2O+MgO+CaO) The value of -Ln (TiO2)-Ln (Y2O3) is between 0.1 and 6. The dielectric constant of the glass finally prepared is less than 5.0 at 1MHz, and the dielectric loss is less than 3.5×10 -3 , Tm(10 2.0 dPa.s)≤1500℃.

[0105] Furthermore, Examples 17 to 24 and Examples 26 to 29 satisfy the following conditions: the mass percentage of SiO2 is 58% to 62%, the mass percentage of B2O3 is 5% to 8%, the mass percentage of P2O5 is 0.4% to 0.7%, the mass percentage of Al2O3 is 12% to 16%, the mass percentage of Na2O is 3.5% to 5.5%, the mass percentage of MgO is 5.5% to 6.5%, the mass percentage of CaO is 6% to 8%, the mass percentage of TiO2 is 0.1% to 0.5%, and the mass percentage of Y2O3 is 0.01% to 0.3%. The dielectric constant of the glass finally prepared at 1 MHz is lower than 4.7, and the dielectric loss is less than 3.3×10 -3 , Tm(10 2.0 dPa.s)≤1500℃.

[0106] In Comparative Example 1, P2O5, TiO2, and Y2O3 were not added, and the dielectric constant at 1MHz was 6.1, which could not meet the requirements of high-frequency microwave communication for glass products. In Comparative Example 2, there was too much B2O3 and no Na2O and Y2O3 were contained, so the glass finally prepared was devitrified and had poor uniformity, and all properties were affected. In Comparative Example 3, there were no alkali metal ions P2O5, Na2O, CaO, TiO2, and Y2O3, so more free oxygen could not be provided, and the melting temperature increased, which increased the difficulty of preparation. In Comparative Example 4, the mass percentage of Y2O3 was too high, and in Comparative Example 5, the mass percentage of TiO2 was too high, so the glass finally prepared was devitrified and had poor uniformity, and the high content of high-field-strength ions would increase the melting temperature and increase the difficulty of production. In Comparative Example 6, the sum of the mass percentages of MgO and CaO was less than 4%, the content of alkaline earth metal oxides was less, the fluxing effect was poor, more free oxygen could not be provided, its melting temperature was high, and the dielectric properties of the sample were poor, which could not meet the requirements of dielectric glass. The mass percentage of TiO2 in Comparative Example 7 is lower and, (-a) The value of -ln(b)-ln(c) is greater than 6, and the dielectric constant and dielectric loss of the glass finally prepared are high, and the dielectric properties are poor. In Comparative Example 8, the Al2O3 content is low, and the formed aluminum oxide tetrahedral network structure is insufficient, resulting in glass phase separation and the formation of silicon-rich and boron-rich phases, thereby causing the prepared glass to lose transparency.

[0107] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0108] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A glass, characterized in that: The glass comprises the following components by mass percentage: SiO2 56%~64%, B2O3 4%~9%, P2O5 0.1%~1%, Al2O3 10%~17%, Na2O 2%~7%, MgO 4%~8%, CaO 4%~10%, TiO2 0.1%~1.5% and Y2O3 0.01%~1%.

2. The glass according to claim 1, characterized in that The glass comprises the following components in percentage by mass: SiO2 58%-62%, B2O3 5%-8%, P2O5 0.4%-0.7%, Al2O3 12%-16%, Na2O 3%-6%, MgO 5%-7%, CaO 5%-9%, TiO2 0.1%-0.9% and Y2O3 0.01%-0.5%.

3. The glass according to claim 2, characterized in that The glass comprises the following components in percentage by mass: SiO2 58%-62%, B2O3 5%-8%, P2O5 0.4%-0.7%, Al2O3 12%-16%, Na2O 3.5%-5.5%, MgO 5.5%-6.5%, CaO 6%-8%, TiO2 0.1%-0.5% and Y2O3 0.01%-0.3%.

4. The glass according to any one of claims 1 to 3, characterized in that: The sum of the mass percentages of the Na2O, the MgO and the CaO is a, the mass percentage of the TiO2 is b, the mass percentage of the Y2O3 is c, and e is satisfied. (-a) The value of -ln(b)-ln(c) is 0.1~6.

5. The glass according to any one of claims 1 to 3, characterized in that: The glass further comprises the following components in percentage by mass: 0.1% to 0.5% of a clarifier; Optionally, the clarifier is selected from NaCl.

6. The glass according to any one of claims 1 to 3, characterized in that: The glass satisfies at least one of the following characteristics: (1) At 1 MHz, the dielectric constant of the glass is less than or equal to 5.5; (2) At 1 MHz, the dielectric loss of the glass is less than or equal to 3.8×10 -3 ; (3) In 10 2.0 dPa.s, the melting temperature of the glass is less than 1500°C.

7. A method for preparing glass, characterized in that: The steps include: Providing raw materials according to the components of the glass according to any one of claims 1 to 6, and mixing the raw materials to prepare a mixture; melting the mixture to prepare molten glass; and The glass liquid is subjected to molding and annealing treatment in sequence to obtain the glass.

8. The method for preparing glass according to claim 7, characterized in that: The temperature of the annealing treatment is 560°C to 620°C.

9. A glass fiber, characterized in that: The material of the glass fiber includes the glass according to any one of claims 1 to 6.

10. An electronic device, characterized in that: The invention comprises the glass according to any one of claims 1 to 6 or the glass fiber according to claim 9.

Citation Information

Patent Citations

  • Glass material

    CN111423111A

  • Low dielectric constant and low dielectric loss glass fiber compositions, glass fibers and their applications

    CN114933418A

  • Low-dielectric glass fiber capable of being molded at low temperature

    CN115321824A

  • Alkali-containing glass, preparation method thereof, glass-containing product, electronic product and application

    CN116789361A

  • Sodium aluminosilicate glass with low dielectric constant and dielectric loss and preparation method thereof

    CN117776520A

Cited By

  • Boron aluminum silicate glass, preparation method thereof, glass product and electronic device

    CN119977321A